Biodiesel Production from Waste Cooking Oil by Alkaline Transesterification Process - Alkinani, Sudad Asaad; Al-Mousawi, Adnan A.; Okash, Anfas N.; Moyel, Mohammad Salim; Alyousif, Nassir Abdullah; Neamaa, Haider Hashim (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
The depletion of fossil fuels, coupled with frequent instability in their prices and environmental concerns related to the drawbacks of full dependence on conventional fossil fuels. considerably, biodiesel is found to be an ideal source of fuel that can efficiently replace conventional fuel diesel. Among various raw materials that can be exploited to produce biodiesel, waste cooking oils are highly recommended as an economically attractive option for biodiesel production. However, the high content of free fatty acids (FFA) in waste cooking oils presents the main barrier to the transesterification process. Therefore, in the current study, two types of waste cooking oils (WCO) collected from homes and restaurants were tested and the percentage of FFA in them was determined through a titration process. The results showed that the percentage of FFA in used cooking oils collected from homes was (1.193%), in contrast with (2.0096%) in WCO observed from the restaurant samples. Thus, WCO collected from homes was candidate to produce biodiesel and it was characterized using FTIR. Transesterification process was carried out in the presence of an alkaline catalyst (KOH), and the yield of biodiesel was reached to 85.4% in the presence of a 1% catalyst at 65 °C degrees and methanol to oil ratio of 6:1 for 90 min. The resulting biodiesel was characterized using FTIR and GC-MS, its properties such as density, kinematic viscosity, cloud point, and pour point were diagnosed as good biodiesel properties based on ASTM standards. The results showed that the alkali-catalyzed transesterification process is an effective way to produce biodiesel from WCO as a source of energy in addition to reducing environmental pollution.